PENGGUNAAN GAYA BAHASA DALAM PUISI KARYA SISWA KELAS VIII SMP NEGERI 27 MALANG - Kuncoro, Condro Ayu Mukti; Sulistyorini, Dwi (Hiski Malang, 2022)
Poetry is one of the standards for junior high school (SMP) students' literary abilities. In poetry, there is definitely a language style that functions to beautify the language in poetry. Likewise with poems written by class VIII A students at SMPN 27 Malang. Based on this, the aim of this research is to reveal the use of language styles in students' poetry, so that the types and forms of use of language styles are known and students' abilities in applying diction in poetry. The research used is qualitative. The data sources contained in this research are 34 poems written by students. From the results of the analysis, it was found that sixteen (16) types of language styles were obtained, with a total of 79. The language styles found include: the first is rhetorical reticence with the highest number of occurrences of around 22 data, then followed by the metaphor, hyperbole and personification language styles with 9 data, followed by the anaphora language style with 6 data. There are other language styles such as rhetorical questions and associations with 4 data each, followed by synecdoche pars pro toto and repetition with 3 data. Next there are the language styles of allegory, tautology, synecdoche totem pro parte which both amount to 2 data, then there are also the language styles of epic parable, simile, pleonasm, and alliteration which each have 1 data. The forms of language style units obtained from students' poetry are in the form of word units, sound units and sentence units. Finally, students' ability to apply denotative and connotative meaningful diction in poetry.